Kebangkitan Tubuh yang Mulia: Prespektif Alkitab Tentang Kehidupan Setelah Mati (Jurnal Pendidikan Agama dan Teologi, 2025)
The resurrection of the body is a key foundation of the Christian faith, as it demonstrates the power of Jesus to overcome death and sin, and provides hope for life after death for His followers. This teaching is clearly presented in the Bible. Many people wonder about the condition of the soul after death. Whether the resurrection of the body is in accordance with the teachings of the Bible, how the resurrection process takes place, whether there is a difference between the resurrection for believers and unbelievers. This article therefore aims to provide an in-depth insight into the concept of bodily resurrection in the Bible, including key verses. The glorious resurrection of the body is the essence of Christian hope and a promise that changes the way believers view life and death. By understanding the Bible's teaching on resurrection, Christians can find comfort, motivation, and purpose in their lives, as well as confidence in a future filled with promise and glory. This article is expected to be a source of reflection and a deeper understanding of the resurrection of the body in the context of Christian faith.” This writing is done using a descriptive qualitative method, which is using literature from books or journal articles that have been made. The Bible teaches that death is not the end of everything, but rather a transition to the promised resurrection. This concept is rooted in the resurrection of Jesus.